Pengembangan Model Pembelajaran Discovery Learning dengan Media Kartu Kosakata untuk Meningkatkan Kemampuan Menggunakan Kalimat Lengkap Siswa Kelas IV Sekolah Dasar Negeri Girijaya - Heri Sugriwa; Iis Ristiani (Institut Nalanda, 2024)
This research aims to illustrate how the development of a discovery learning model using vocabulary card media can improve the ability to use complete sentences in fourth grade elementary school students. This type of research is development research. Data was collected through questionnaires and interviews, with data sources coming from teachers and students in the six classes studied. Data was analyzed using quantitative and qualitative descriptive methods, starting by changing the qualitative assessment to quantitative to get a score, then calculating the average score, changing it back to a qualitative assessment, as well as explaining the data, discussing the research results, and concluding. The research results show that: (1) based on needs analysis, the learning model desired by students and teachers is a model that actively involves students and fosters curiosity to discover something. The learning media needed is media that is cheap, interesting, easy to use, and can increase students' vocabulary. (2) The principles of preparing learning models include the principles of motivation, experience, discovery, cooperation, language and repetition. (3) Developing a discovery learning model using vocabulary card media produces products in the form of learning models and media which are realized in the form of guidebooks.